Evaluation of real‐life clinical outcomes in Australian youth with type 1 diabetes on hybrid closed‐loop therapy: A retrospective study. (31st May 2022) - Vijayanand, Sathyakala; Stevenson, Paul G; Broad, Elizabeth; Davis, Elizabeth A; Taplin, Craig E; Jones, Timothy W; Abraham, Mary B
Abstract : Aim: To determine the clinical outcomes and evaluate the perspectives of children with Type 1 diabetes (T1D) and their parents managing their child on hybrid closed‐loop (HCL) therapy. Methods: Children with T1D on HCL attending a tertiary diabetes centre between April 2019 and July 2021 were included. A retrospective analysis of glycaemic data was conducted to determine the clinical outcomes. Time spent in closed loop, time in target glucose range (TIR 3.9–10 mmol/L), hypoglycaemia and hyperglycaemia were collected at baseline, 4 weeks, 3 and 6 months post‐HCL. User experience was assessed by questionnaires administered to parents of children with T1D. Results: Seventy‐one children, mean (SD) age of 12.2 (3.2) years were commenced on HCL. Ten (14%) discontinued HCL use, with 60% discontinuing within the first 6 months. Glycaemic outcomes were analysed in 52 children. Time spent in closed loop was 78 (21) % at 4 weeks, declined to 69 (28) % at 3 months ( P = 0.037) and 63 (34) % at 6 months ( P = 0.001). The mean %TIR increased from 59.8 at baseline to 67.6 at 3 months and 65.6 at 6 months with a mean adjusted difference of 7.8% points [95% CI 3.6, 11.9] and 5.5% points [95% CI 1.4, 9.5], respectively. There was a reduction in time > 10 mmol/L and time < 3.9 mmol/L from baseline to 6 months. Although families faced challenges with technology, better glucose control with reduced glycaemic fluctuations were reported. Conclusions: HCL therapy is associated with improved glycaemia; however, adequate support and education are required for best outcomes.